2002
DOI: 10.1046/j.1526-100x.2002.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Wyoming Big Sagebrush Density: Effects of Seeding Rates and Grass Competition

Abstract: The mining industry commonly seeds shrubs and grasses concurrently on coal‐mined lands of northeastern Wyoming, but ecological interactions between seeded shrubs and grasses are not well documented. Artemisia tridentata Nutt. ssp. wyomingensis (Beetle and Young) (Wyoming big sagebrush) is the dominant pre‐mining shrub on many Wyoming mine sites. Despite past failures to establish Wyoming big sagebrush, the Wyoming Department of Environmental Quality, Land Quality Division's rules and regulations require establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 16 publications
5
49
0
Order By: Relevance
“…During 2004 sampling, individuals of big sagebrush averaged 6.66 cm in height. The open canopy available in the more shallow topsoil replacement areas accounted for germination and growth of shrubs at least three years after seeding (Owens and Norton, 1989;Williams et al, 2002). Comparison of Reclaimed Treatments to Older Reclaimed Area at NARM The oldest shrub-grassland reclaimed area at NARM, seeded with the mixture outlined in Table 1, was seeded in 1991; replacement topsoil depth in this area was 56 cm, but source of the replacement topsoil was direct-hauled not stockpiled as in the current study.…”
Section: Species Compositionmentioning
confidence: 68%
“…During 2004 sampling, individuals of big sagebrush averaged 6.66 cm in height. The open canopy available in the more shallow topsoil replacement areas accounted for germination and growth of shrubs at least three years after seeding (Owens and Norton, 1989;Williams et al, 2002). Comparison of Reclaimed Treatments to Older Reclaimed Area at NARM The oldest shrub-grassland reclaimed area at NARM, seeded with the mixture outlined in Table 1, was seeded in 1991; replacement topsoil depth in this area was 56 cm, but source of the replacement topsoil was direct-hauled not stockpiled as in the current study.…”
Section: Species Compositionmentioning
confidence: 68%
“…According to the Wyoming State Rules and Regulations (2017), variable soil depths are also allowable: ''Soil thickness may also be varied to the extent such variations help meet the specific revegetation goals identified in the permit.'' Some studies performed in the western USA showed that revegetation results can be affected by varying soil depths (Buchanan et al 2005;Bowen et al 2005;Williams et al 2002). To enhance the growth of hard-to-establish shrubs such as big sagebrush (Artemisia tridentata), NARM has developed two soil replacement depth ranges: typical (15-40 cm) and deep (40-120 cm).…”
Section: Reclamation Planmentioning
confidence: 99%
“…Specific studies conducted in the western USA states discuss the effects of mining and reclamation approaches on geomorphic processes (Toy and Black 2000), soil properties, and management (Pinchak et al 1985;Schroeder and Vinning 1993;Buchanan et al 2005;Reynolds and Reddy 2012), and re-vegetation strategies and methods (Williams et al 2002;Schuman et al 2005;Strom et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On a mine reclamation project in Wyoming, sagebrush seed was broadcast seeded using a precision broadcast seeder with cracked corn to accomplish uniform seed distribution and flow through the seeder. Seeding rates between 1 to 4 kg/ha PLS were used and had sagebrush establishment densities of 1.0 to 4.5 shrubs/m2 after 6 years (Williams, Schuman, Hild & Vicklund 2002).…”
Section: Broadcasting Sagebrushmentioning
confidence: 99%